Simulation Study of the Velocity Profile and Deflection Rate of Non-Newtonian Fluids in the Bend Part of the Pipe - Defeng Wang; Zhanbo Cheng; Qingwen Shi; Jinhai Zhao; Helmut Mischo (Geofluids)
As resource extraction moves deeper underground, backfill mining has received a lot of attention from the industry as a very promising mining method that can provide a safe workplace for workers. However, the safe and efficient transport of fill slurry through pipelines still needs more exploration, especially in the bend section. In order to investigate the flow characteristics and velocity evolution of the slurry in the bend section of the pipe, a three-dimensional (3D) pipe model was developed using the computational fluid dynamics software Fluent, and nine sets of two-factor, three-level simulations were performed. Furthermore, a single-factor analysis was presented to investigate the effects of the two main influencing factors on the shifting of the maximum velocity of the slurry towards the distal side in the bend section, respectively. Then, the response surface analysis method was applied to the two-factor analysis of the maximum velocity shift and the weights of the two influencing factors were specified.